Emotional contagion in online groups as a function of valence and status - Kane, Aimée A.; van Swol, Lyn M.; Sarmiento-Lawrence, Irene G. (Computers in human behavior, 2023)
A pre-registered lab experiment with a two (valence of the partner's emotional language: positive, negative) by two (partner status: equal, higher) between-subjects factorial design was conducted. Results suggests that emotional language of group members plays an important role in emotional contagion. Using an online chat tool, 235 undergraduate students participated in a simulated two-person group tasked with coming to a position on a social issue. To systematically manipulate emotional language displays, the partner was an electronic confederate that was enacted using a computer program. Results supported three emotional contagion and two group process hypotheses. The valence of a partner's emotional language was contagious and significantly affected both the positive and negative felt emotions of the participant. Displayed emotional contagion also occurred; participants displayed significantly more negative emotional language as a function of the valence of their partner's emotional language. A partner's use of positive emotional language increased perceived group reflection and reduced conflict, both relational and task. An exploratory hypothesis was also supported: mimicry of negative emotional language mediated emotional contagion for those working with a higher status partner, but not for those working with an equal status partner. Theoretical contributions and implications are discussed. •Experiment shows emotional language plays an important role in emotional contagion.•Pre-registered test of emotional contagion from a partner in an online chat group.•Contagion impacted positive and negative felt emotion and negative emotion displays.•Mimicry mediated negative contagion for those working with a high-status partner.•Positive contagion strengthened group reflection and dampened conflict.